Education for citizenship in Europe : European policies, national adaptations and young people's attitudes - Keating, Avril (Palgrave Macmillan, 2020)
This book examines the evolving relationship between the nation-state, citizenship and the education of citizens, exploring the impact European integration had on national policies towards educating its citizens and citizenship